Community structure of phytoplankton in Downstream of the Segedong River, Kubu Raya Regency, West Kalimantan - Syifa Ulva Nara Dita; Entin Daningsih; Wolly Candramila (Program Studi Akuakultur, Fakultas Pertanian, Universitas Almuslim, 2023)
The Segedong River flows between the Tanjung Prapat Muda Mangrove Protected Forest in Kubu Raya Regency. Mangrove forests contribute nutrients to water. However, nutrients and fluctuative environmental conditions influence the existence of phytoplankton. People’s settlements and fish farming activities downstream of ​​the Segedong River influence environmental conditions. Research on phytoplankton is needed to determine the quality of the Segedong River. The aim of this research is to determine the abundance and diversity of phytoplankton in the downstream Segedong River. Sampling was carried out in the dry and rainy seasons using a survey method at 3 stations. Water physicochemical factors are measured in situ and ex situ. The identified phytoplankton species are then calculated for their abundance, diversity index, evenness, and dominance. 59 phytoplankton species are categorized into 6 classes, including Bacillariophyceae (35 species), Dinophyceae (15 species), Chlorophyceae (4 species), Cyanophyceae (3 species), Chrysophyceae (1 species) and Xanthophyceae (1 species). The phytoplankton abundance obtained in both seasons at all stations ranged from 1,314-10,185 Ind.L-1 or categorized into oligotrophic to mesotrophic. The diversity index ranges from 1.99-2.88 in the medium category. The evenness index ranges from 0.53-0.80, which is in the medium to high category, while the dominance index is low <0.4.